1996
DOI: 10.1046/j.1365-2249.1996.d01-850.x
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of antigens recognized by coeliac disease autoantibodies and their use in enzyme immunoassay of endomysium and reticulin antibody-positive human sera

Abstract: SUMMARYComponents were isolated from rat liver, sheep lung, rhesus and orang-utan intestine. In enzyme immunoassay, these components detected 57%, 72%, 84% and 88% of human sera containing endomysium and reticulin antibodies (EmA and ARA). At most, 7% of EmA/ARA-negative sera reacted with the antigens. The spectrum of EmA/ARA-positive sera reactive with the various components was different but overlapping. When the antigens of sheep lung and orang-utan intestine were used as a cocktail, 98% of EmA/ARA-positive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

1997
1997
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 23 publications
(24 reference statements)
0
11
0
Order By: Relevance
“…Based on the fact that sera from most celiac patients displayed IgA reactivity to ELISA plate-coupled guinea pig and human transglutaminase and that pre-incubation of sera with this protein reduced EMA reactivity, transglutaminase was proposed as the perhaps exclusive autoantigen of celiac disease [27,31,32]. However, despite the frequent and prominent IgA reactivity to transglutaminase, other studies suggested that also other autoantigens may play a role in celiac disease [28][29][30]. The occurrence of IgA-reactive autoantigens other than tissue transglutaminase would also explain the incomplete association of anti-endomysium and anti-transglutaminase reactivity observed in our study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the fact that sera from most celiac patients displayed IgA reactivity to ELISA plate-coupled guinea pig and human transglutaminase and that pre-incubation of sera with this protein reduced EMA reactivity, transglutaminase was proposed as the perhaps exclusive autoantigen of celiac disease [27,31,32]. However, despite the frequent and prominent IgA reactivity to transglutaminase, other studies suggested that also other autoantigens may play a role in celiac disease [28][29][30]. The occurrence of IgA-reactive autoantigens other than tissue transglutaminase would also explain the incomplete association of anti-endomysium and anti-transglutaminase reactivity observed in our study.…”
Section: Discussionmentioning
confidence: 99%
“…A 85-kDa protein was immunoprecipitated from the IgA fractions of celiac disease patients and identified as tissue transglutaminase by protein sequencing [27]. Although pre-incubation of sera with tissue transglutaminase significantly inhibited endomysial antibody labeling, other authors suggest the occurrence of several antigens as targets for IgA autoantibodies of celiac disease patients [28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…According to SDS‐polyacrylamide gel electrophoresis (SDS‐PAGE) [13]and immunoblot [14]the resulting product (gli/glu) contained ethanol extractable gliadins (α‐, γ‐, ω‐type) known to be accompanied by minor amounts of gliadin‐related low molecular weight (LMW) glutenins [11]. Rabbits were immunized with gli/glu [15]. Immunoglobulin G was isolated from rabbit sera by affinity chromatography on protein A. Antibodies against gli/glu (gliadin antibodies) were affinity purified using gli/glu coupled to Affigel‐10 (Bio‐Rad, Munich, Germany).…”
Section: Methodsmentioning
confidence: 99%
“…Whelan et al showed that an antigen found in human umbilical vein endothelial cells is antigenically similar to that found in reticulin and endomysium 11. Karska et al again suggested that calreticulin is a potential autoantigen12 and Borner et al isolated several structural protein components from various animal tissues 13…”
Section: Commentmentioning
confidence: 99%